Pengaruh Motivasi Intrinsik dan Ekstrinsik terhadap Perencanaan Karir Calon Pendidik: Analisis SEM-PLS pada Mahasiswa FKIP - Handoko, Handoko (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose – This study aims to examine the influence of motivation on the career planning of prospective educators, specifically students of the faculty of teacher training and education, from the perspectives of intrinsic and extrinsic motivation.Method – This research employs a quantitative approach using SEM-PLS to analyze the relationships between independent and dependent variables. Data were collected using questionnaires with a Likert scale to measure each indicator. The study sample consisted of 100 pre-service teacher students from various education programs, including Elementary Teacher Education, Chemistry Education, Physics Education, Biology Education, Guidance and Counselling, Early Childhood Education, Mathematics Education, and Physical Education. Respondents were drawn from different semesters, specifically the first and third semesters. Statistical tests were conducted using outer loading, composite reliability, Average Variance Extracted, P-value, Adjusted R-Square, and F-Square. Findings – The influence of motivation on career planning has a p-value (0,000) < 0.05, indicating a statistically significant relationship. The Adjusted R-Square value of 0.349 demonstrates that 34.9% of the dependent variable (career planning) can be explained by the independent variable (motivation, which includes intrinsic and extrinsic motivation). Research Implications – Practically, the results highlight the importance for educational institutions to design programs that strengthen both intrinsic and extrinsic motivation among prospective educators. Providing career guidance, mentorship programs, and opportunities for professional development can foster better career planning. Theoretically, this research contributes to the body of knowledge in career development studies by confirming the significant role of motivational factors in shaping career planning among future educators.